Identifying priority restoration areas based on ecological security pattern: implications for ecological restoration planning - Yingying Li; Min Wei; Rui Zhou; Huan Jin; Yongsheng Chen; Changjin Hong; Wenting Duan; Qiuyue Li (Ecological Indicators)
The rapid urbanization has exacerbated the deterioration of the ecological environment and the destruction of ecosystem services. Maintaining regional ecological security and enhancing ecosystem stability greatly depend on ecological restoration of territorial space. Scientific identification of priority areas for ecological restoration and rational planning of ecological restoration space have gradually become the research hotspot and the vital issues to be solved. Taking the region around Chaohu Lake as an example, this study combined morphological spatial pattern analysis (MSPA), ecosystem service value (ESV) evaluation and circuit theory to construct ecological security pattern and identify the priority ecological restoration areas. The results showed that: (1) The ecological sources covered an area of 1038.33 km2, dominated by forests and water bodies, which were mainly distributed in the southeast and northwest of the study area. (2) There were 135 ecological corridors with a total length of 1632.21 km, primarily locating in the ecological resources concentration area, and had formed a closely connected ecological network. (3) The priority restoration areas consisted of 47 ecological pinch points, 37 ecological barrier points, and 45 ecological breakpoints, with a total area of 9.53 km2. (4) The ecological restoration planning strategies for priority restoration areas were proposed at three scales (macro, meso, and micro), based on the spatial distribution characteristics of key ecological areas and their land use status. Our study helps to provide important insights and decision support for the future ecological restoration planning and ecological resource sustainable development.